Ayurvedic Management of a Large Cystic Thyroid Nodule (International Journal of Ayurveda and Pharma Research, 2025)
A thyroid nodule is a very common palpable swelling in the thyroid gland. About 95% of thyroid nodules are benign in nature. Thyroid nodules require assessment using suitable diagnostic tests and imaging techniques. Any nodule greater than 1cm should be biopsied to check for malignancy. Thyroid nodules occur more frequently in women than men. Here, presenting a case of a lady with a large cystic thyroid nodule in the left lobe, managed under the outpatient department. She presented with rapidly increasing swelling in her neck associated with pressure symptoms and spasming of hands and legs for 4 days. She was prescribed a combination of Varanadi Kashaya, Punnarnavadi Kashaya, Kanchanara Guggulu, Chandraprabha Vati and Gokshura Choorna internally and Karutta Vattu for external application. By the first follow-up itself (after 10 days), the patient felt symptomatic relief. Investigations repeated after 50 days showed considerable change in the size of the cystic nodule. Similarly, there is cosmetic resolution of the swelling at the 50th day follow up which is evident from the photographs provided.